Analysis of the Application of the Online Learning System (Spada) to Increase Student Learning Activities during the Covid-19 Pandemic - Oktaviandi Bertua Pardede; Nanda Dwi Astri (RIRAI Publisher, 2021)
This study aims to explore student learning activities at the Faculty of Teacher Training and Education, University of Prima Indonesia (Unpri) during the pandemic through Spada. This needs to be done because there are significant differences in the learning system. The transfer of face-to-face learning methods to virtual distance learning, namely Spada, triggers the emergence of a direct effect on student learning activities. This study applies a qualitative descriptive approach with survey methods and semi-experimental methods that apply hypothesis testing. The sampling technique used cluster random sampling with the research sample being Indonesian Language and Literature Education students who were at level 3. This sample was grouped into 4 parallel classes. Observations showed that student learning activities in Spada who consistently attended every meeting were 62.2%. The survey also shows that 52.7% are interested in face-to-face learning. Students are known to often access lecture materials that are not in accordance with the time of admission. And a report on Spada shows that the average material access period lasts less than 20 minutes. Students tend to ignore the resources and learning activities implemented in Spada. The results of the questionnaire confirmed the existence of obstacles in student learning activities through Spada by 47.5%. Researchers also attempted to conduct experiments on the assessment of learning outcomes through the one-way ANOVA test. The result is p>0.05 and shows the acceptance of H0 that there is no difference in student learning outcomes between classes. So it can be proven that the application of Spada has not been able to increase the learning activities of different students during the pandemic.